Still Thriving: A Case Illustrating How COVID-19 Affected Indigenous Health and Wellness - Cranston, Jerome; Whitford, Rina (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
The myriad of social, financial, material health, and educational inequities that continue to plague Indigenous communities was exacerbated by COVID-19. In order to place on spotlight on them, this case follows Star, an Indigenous Student Success Coordinator, as she navigated the policies and practices couched in the rhetoric of supporting the success, health and wellness of students and families during a global pandemic. The case and teaching notes that follow illustrate the limitations that Westernized models of health and wellness create for Indigenous and non-Indigenous educators when it comes to maintaining their students’ and own well-being. As an alternative to the dominant Westernized models, the teaching notes offer a more holistic and integrated model of Indigenous health and wellness. The elements of the model situate health and wellness as encompassing all aspects of an individual’s life by connecting them relationally to their families and communities, nations, and the land.